Aa opinion survey of teachers on the use and applicaton of information and communication technologies in higher education. - Araiza Vázquez, María de Jesús; Dörfer, Claudia (2012)
This research was conducted to address the need for training and support required by teachers in a Mexican institution of higher education in the use and integration of Information and Communication Technologies (ICT) in their teaching. To achieve this, we conducted a study to identify the mixed type of training and support needs with teachers in the area of ICT for education. In the process of data collection instruments were used as the questionnaire and semi-structured interviews, which were applied to three groups of teachers who formed the sample selected for this study. To respond to the research questions, namely what are the training needs in the field of ICT require teachers? and What are the types of support they require teachers to use ICT?, there were a series of individual interviews to six teachers in this institution, three key pieces in the administration of it. In addition, an opinion questionnaire applied to 95 teachers. Overall, the study identified the needs and support that teachers need to integrate ICT in their work and also made clear the need to establish, for academic communities, measures and criteria to guide the formation of the same in the use and application of technological tools.